Elemental spectra from the first ATIC flight - Ahn, H. S.; Adams, J. H.; Bashindzhagyan, G.; Batkov, K. E.; Changv, J.; Christl, M.; Fazely, A. R.; Ganel, O.; Gunasingha, R. M.; Guzik, T. G.; Isbert, J.; Kim, K. C.; et al. (LSU Digital Commons, 2005)
The Advanced Thin Ionization Calorimeter (ATIC) instrument is a balloon-borne experiment designed to measure the composition and energy spectra of Z = 1 to 26 cosmic rays over the energy range from ̃ 1011 to 10 eV. The instrument consists of a silicon matrix charge detector, plastic scintillator strip hodoscopes interleaved with graphite interaction targets, and a fully active Bismuth Germanate (BGO) calorimeter. ATIC had two successful Long Duration Balloon flights launched from McMurdo Station, Antarctica in 2000 and 2002. In this paper, preliminary energy spectra of C and O measured during the first 16-day flight are presented.